PEREMPUAN DAN GENDER DALAM KORUPSI DI INDONESIA - Febri Handayani (Study Program of Islamic Family Law, Syari'ah Faculty, University of Al-Hikmah Indonesia, 2022)
This paper examines the involvement of women in corruption in Indonesia. Today people who commit corruption no longer recognize gender. The perpetratorsare of corruption are no longer men, but also the perpetrators are women. The number is not as much as men, but the number is increasing from year to year, with various professionals backgrounds. Even sadly, women are objects of gratification to facilitate affairs. Based on this, by researching normative law, and using a statutory approach as well as a conceptual approach. The results of the study indicate that women who occupy strategic positions are able to be a balancer because women have more sensitive to taste, refinement of mind, and can play a central role with its natural nature. Corruption is an immoral act that is used to carry out actions with institutional integrity standards. Increased involvement of women not as victims of corruption but as agents of change involved is very important to solve problems. But on the other hand, it is known that the factors that cause corruption can be seen from factors that come from within the perpetrators of corruption, but can also come from outside the perpetrators. Prevention of corruption can be done by means of the extent to which anti-corruption values can be internalized within oneself and changes through an integral approach to fighting corruption.